Demographic Characteristics Related to First Married Age in Indonesia - Najib, Najib; Triwijayanti, Urip; Utomo, Wahyu (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Quantitative population growth but does not compensates with the quality will be a problem. One of the efforts to reduce the population growth rate is the age of first marriage. Based on BPS data in 2017, early marriage in Indonesia is 25.71 percent, meaning that in every 100 marriages, there are 25 couples less than 18 years. This study aims to study the factors affecting the age of first marriage (UKP) in Indonesia. The data used were the results of the 2017 RPJMN Survey with a sample of 51,493 people. The data was taken by systematic random sampling, then the unit of analysis was taken FAW (15-49 years) married as many as 40,268 respondents. The variables studied included residence, wealth quintile, education level, employment status, and age at first marriage. The analysis was performed using descriptive and inferential methods using binary logistic regression models. The results showed 21,405 (53.2%) women at first marriage were more than 20 years old. Meanwhile, those under 20 years of age totaled 18,863 people (46.8%). Statistically, there is a significant relationship between the variables of age at first marriage and residence, wealth quintile, education level, and employment status. Women aged 15-49 years tend to marry or have a high risk of experiencing the age of first marriage over 20 years are those who live in urban areas, high economic status, highly educated, and working.